Treating daytime blindness with eye movement desensitization and reprocessing: a case report - Altunbaş, Fatma Dilara (The European Research Journal, 2018)
Medically unexplained physical symptoms (MUPS) is physical complaints which are difficult to diagnose by the medical analysis. According to studies, traumatic life events, and adverse childhood experiences underlie the occurrence of MUPS. Eye movement desensitization and reprocessing (EMDR) is a therapy that is applied to treat post-traumatic stress disorder (PTSD), and recently it is known that EMDR can be used in the treatment protocol of other mental health problems. This case report demonstrates efficaciousness of EMDR therapy on PTSD-related daytime blindness (hemeralopia).